Peningkatan Kemampuan Bahasa Inggris bagi Masyarakat Nelayan di Donggang, Taiwan - Eko Suhartoyo; Fitria Dewi Navisa; Syayidah Muslimah; Fabian Akbar Nugraha (Universitas Muhammadiyah Semarang, 2025)
English proficiency is essential for expanding economic and social opportunities in the era of globalization. However, the fishing community in Donggang, Taiwan, still faces difficulties in learning English due to time constraints, limited access to technology, and varying levels of language proficiency. This community service program aims to enhance the English language skills of the Donggang fishing community to broaden their economic prospects and social interactions in the global arena. The program employs a flexible approach using blended learning methods and materials relevant to the participants’ daily lives. The main challenges encountered include limited time, technology access, and differences in English proficiency levels. To address these challenges, solutions implemented include the use of printed materials, group-based learning, and practical speaking and writing exercises. The results demonstrate significant improvements in participants’ speaking, writing, and vocabulary related to their work as fishermen. Participants also showed increased confidence in communicating in English, along with motivation to continue independent learning after the program’s conclusion. Moreover, the program successfully fostered a learning environment that supported camaraderie and collaboration among participants. Overall, this program not only enhanced the participants’ English skills but also opened new economic opportunities and enriched their social interactions. The program has delivered sustainable positive impacts and can serve as a model for other community service initiatives aimed at empowering local communities through relevant, community-based education.